A Systematic Literature Review: The Impact of Imported Products on the Competitiveness of MSMEs in Indonesia - Hardini, Han Tantri; Subroto, Waspodo Tjipto; Sakti, Norida Canda (PT. Maju Malaqbi Makkarana, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. However, the increasing presence of imported products can pose a challenge to the competitiveness of MSMEs. This study aims to explore the available literature on the impact of imported products on the competitiveness of MSMEs in Indonesia through a systematic literature review approach reviewed from the factors that influence the competitiveness of MSMEs, the impact of imported products to Indonesia on the competitiveness of MSMEs, strategies to increase the Competitiveness of MSME products so that they can compete with imported products and government policy recommendations for MSMEs to be able to compete with imported products. The results of this study provide insight into overcoming the negative impact of the rise in imported products on the growth of MSMEs amidst the flow of globalization